The Effectiveness of Group Counseling Services Through Feedback Techniques to Improve Fine Arts Learning Outcomes - Widiana, I Wayan (International Journal of Multidisciplinary Sciences, 2024)
The objectives in this study are: To determine the effectiveness of implementing group counseling services through feedback techniques in improving Fine Arts Learning Outcomes. The results of the study show that group counseling through feedback techniques in the subject of Fine Arts is an alternative that can be used as a solution in providing assistance with problems related to the learning process in the subject of Cultural Arts. This is inseparable from the essence of group counseling and feedback, namely emphasizing the reinforcement provided by the teacher so that students or counselees are able to foster motivation which later has implications for the speed in receiving the material presented, given that in general art material is more dominated by practical activities. So that group counseling services with feedback techniques can improve learning outcomes in Fine Arts, especially in the Basic Competencies of Self-Expression through works of pure art that are developed from elements of Indonesian fine arts. From the results of the study there was improvement in each cycle. Namely from pre-cycle to cycle I, from pre-cycle to cycle II, and from cycle I to cycle II, with improvement in learning outcomes scores, respectively by 1.75 points, 2.94 points, and 4.69 points. Meanwhile, classical completeness also increased. From 47% in pre-cycle to 65.63% in cycle I and increased again to 94% in cycle II.